617.PROCESSES OPTIMIZATION AND REDUCTION OF OPERATIONAL COSTS– CASE IN INSURANCE COMPANY - Vesna, Gjorceva; Gligoce, Vrtanoski (MECHANICAL ENGINEERING – SCIENTIFIC JOURNAL, 2020)
The insurance industry is mainly based on its primary activity which is exercising the right to claim payment in case of insured case occurrence, arising unexpectedly as a sudden event, not in any way related to the will of the insured. For this purpose, work organization in an insurance company implies application of a complex and well designed system of activities and processes. Each separate process should be functional in both directions. The first one should be directed towards itself, thus providing high quality performance of the planned process activities. The second one is to be focused on its complementary functioning together with the remaining processes included within the insurance business. Clearly defined processes, based on empirical techniques and methods contribute to greater effectiveness and efficacy which result in greater profitability as a final objective in the work of one insurance company. The research in this paper aims to ascertain the impact of improved processes of operational cost reduction and increase of profitability as the ultimate goal.